Murder at King's Crossing [large type] - Penrose, Andrea (Penrose, Andrea. Wrexford & Sloane historical mystery, 2024)
"Celebration is in the air at Wrexford and Charlotte's country estate as they host the nuptials of their friends, Christopher Sheffield and Lady Cordelia Mansfield. But on the afternoon of the wedding, the festivities are interrupted when the local authorities arrive with news that a murdered man has been discovered at the bridge over King's Crossing, his only identification an invitation to the wedding. Lady Cordelia is horrified when the victim is identified as Jasper Milton, her childhood friend and a brilliant engineer who is rumored to have discovered a revolutionary technological innovation in bridge design. That he had the invitation meant for her cousin Oliver, who never showed up for the wedding, stirs a number of unsettling questions. Both men were involved in the Revolutions-Per-Minute Society, a scientific group dedicated to making radical improvements in the speed and cost of transportation throughout Britain. Is someone plotting to steal Milton's designs? And why has her cousin disappeared? Wrexford and Charlotte were looking forward to spending a peaceful interlude in the country, but when Lady Cordelia resolves to solve the mystery, they offer their help, along with that of the Weasels and their unconventional inner circle of friends."--